A ratiometric electrochemical strategy based on Fe (iii) and Pt (iv) for immobilization-free detection of Escherichia coli. Issue 25 (17th June 2022) - Su, Lixia; Su, Yonghuan; Liu, Bingqian
Abstract : The ratiometric electrochemical strategy for immobilization-free detection of Escherichia coli was constructed by using a capture DNA-polyaniline/copper ferrite nanoparticles/graphene oxide (cDNA-PANI/CuFe2 O4 /GO) composite as capture probes. Abstract : A new ratiometric electrochemical strategy for immobilization-free detection of Escherichia coli ( E. coli ) was constructed by using a capture DNA-polyaniline/copper ferrite nanoparticles/graphene oxide (cDNA-PANI/CuFe2 O4 /GO) composite as capture probes, which has a high specific surface area and good magnetic properties. Then trigger DNA/Au nanoparticles (tDNA/Au NPs) were used as signal amplification labels, and Pt (iv ) and Fe (iii ) were chosen as the signal probes. In the presence of targets, the sandwich format among cDNA-PANI/CuFe2 O4 /GO, E. coli and auxiliary DNA (aDNA) was realized by using the aptamer recognition system. Then, the tDNA/Au binding could be anchored on the sandwich format due to the principle of base complementation between unpaired aDNA and tDNA. And the unbounded tDNA of tDNA/Au NPs could bind an amount of Pt (iv ). After separation using a magnet, a handful of unbound Pt (iv ) which remained in the supernatant reacted with a large number of Fe (iii ) ions, leading to a markedly increased I Fe(iii ) / I Pt(iv ) value. Oppositely, the sandwich format could not appear in the absence of targets, and even the tDNA/Au could not be immobilized on it. So, the redox reaction between a large amount of Pt (iv ) residue in the supernatant and Fe (iii ) was significantly successful, causing a low I Fe(iii ) / I Pt(iv ) value. Under optimal conditions, we found that I Fe(iii ) / I Pt(iv ) was linearly related to the logarithmic E. coli concentration with a low limit of detection (1.862 × 10 3 cfu mL −1 ). This devised ratiometric electrochemical method may develop into a powerful and effective means for the detection of E. coli in real samples, which may also be developed as a universal tool for another microorganism.